2016
DOI: 10.3389/fvets.2016.00095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Selection of Bacillus Species Based on Enzyme Production, Antimicrobial Activity, and Biofilm Synthesis as Direct-Fed Microbial Candidates for Poultry

Abstract: Social concern about misuse of antibiotics as growth promoters (AGP) and generation of multidrug-resistant bacteria have restricted the dietary inclusion of antibiotics in livestock feed in several countries. Direct-fed microbials (DFM) are one of the multiple alternatives commonly evaluated as substitutes of AGP. Sporeformer bacteria from the genus Bacillus have been extensively investigated because of their extraordinary properties to form highly resistant endospores, produce antimicrobial compounds, and syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 62 publications
4
113
1
1
Order By: Relevance
“…In this regard, our results clearly demonstrated that the B. amyloliquefaciens US573 strain produces simultaneously multiple extracellular hydrolytic enzymes, as was the case for the commercial feed additive Rovabio® Max (ADISSEO). This is likely to ensure a synergistic enzyme‐mediated improvement of nutrient bioavailability and feed conversion rate as a consequence of enhanced digestibility of the antinutritional factors present within feed ingredients of poultry diets …”
Section: Resultsmentioning
confidence: 99%
“…In this regard, our results clearly demonstrated that the B. amyloliquefaciens US573 strain produces simultaneously multiple extracellular hydrolytic enzymes, as was the case for the commercial feed additive Rovabio® Max (ADISSEO). This is likely to ensure a synergistic enzyme‐mediated improvement of nutrient bioavailability and feed conversion rate as a consequence of enhanced digestibility of the antinutritional factors present within feed ingredients of poultry diets …”
Section: Resultsmentioning
confidence: 99%
“…The CE mechanisms by which Bacillus protects aquatic animals against pathogen infection can be extended to immunity enhancement. Li et al (2007) found that L. vannamei fed B. licheniformis exhibited a significant increase in phenoloxidase and superoxide dismutase activities, and showed a decrease in the population of Vibrio sp. in the intestine as compared with the control shrimp.…”
Section: Aquaculturementioning
confidence: 97%
“…Several Bacillus sp. are able to produce a variety of extracellular enzymes including amylase, protease, lipase, phytase, cellulase and xylanase (Latorre et al 2016). These enzymes have been used in animal nutrition to assist in the digestion of feed and improve nutrient absorption.…”
Section: Functional Criteria For Desirable Probiotic Propertiesmentioning
confidence: 99%
“…The Bacillus species have the advantage of possessing the spore‐forming ability coupled with acid and bile tolerance properties along with the antagonistic activity against major gut pathogens and susceptibility to most of antibiotics . In addition, they produce various extracellular hydrolytic enzymes, which can help in improving digestion and exhibit the ability to form biofilm contributing to the protection of the gut epithelium from adherence of opportunistic pathogenic microorganisms and helping to withstand harsh environmental conditions and physical stresses .…”
Section: Introductionmentioning
confidence: 99%